EFFECT OF THINK PAIR SHARE IN GUIDED INQUIRY ON STUDENT MOTIVATION AND LEARNING OUTCOMES - Triana, Siti Hardiyanti (Yayasan Amanah Nur Aman, 2025)
This research is a quasi-experimental study aimed at determining the effect of the think-pair-share method in the guided inquiry learning model on student motivation and learning outcomes. The independent variable in this research is the think-pair-share method in the guided inquiry learning model. Dependent variables are learning motivation and learning outcomes in acid-base material. The sample in this research, which was selected by simple random sampling, consisted of 2 classes, which were divided into an experimental class and a control class, each consisting of 32 students, determined by using a simple random sampling technique. The research data were obtained using questionnaires of learning motivation and tests of learning outcomes in acid-base material, which were analyzed by the t-test for learning motivation and the Mann-Whitney test for learning outcomes. The result of the hypothesis was t-calculated = 1.739 at α = 0.05, obtained t-table = 1.669, so that t-calculated > t-table. It is shown that there is an effect of the think-pair-share method in the guided inquiry learning model on student learning motivation. For the learning outcomes, Z-calculated = 3.31 at α = 0.05, obtained Z-table = 1.64. Since Z-calculated > Z-table, therefore H1 is accepted and H0 is rejected. It is shown that there is an effect of the think-pair-share method in the guided inquiry learning model towards student learning outcomes.